2020
DOI: 10.3390/s20205814
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Playing Position, Match Half, and Match Day on the Trunk Inclination, G-Forces, and Locomotor Efficiency Experienced by Elite Soccer Players in Match Play

Abstract: The rapid growth of wearable sensors has allowed the analysis of trunk kinematics during the match, which is necessary for having a better understanding of the postural demands of soccer players. However, some contextual variables may have an impact on the physical demands of the players. This study aimed to analyze the effect of three contextual variables (playing position, match half, and match day) on the sagittal trunk inclination, G-forces, and locomotor efficiency experienced by soccer players in match p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…11 However, this pattern was not observed for other external load variables such as distance covered, sprinting distance, total accelerations, or total decelerations. 11 This is also consistent with other investigations, which observed that playing position had no significant effect on the locomotor efficiency (ie, PL TOTAL per meter covered) 28 and that the variance in the PL TOTAL was not significantly explained by the positional role during elite soccer match play. 1 Nevertheless, other researchers also showed that positional differences in PL TOTAL may exist across playing positions.…”
Section: Discussionsupporting
confidence: 89%
“…11 However, this pattern was not observed for other external load variables such as distance covered, sprinting distance, total accelerations, or total decelerations. 11 This is also consistent with other investigations, which observed that playing position had no significant effect on the locomotor efficiency (ie, PL TOTAL per meter covered) 28 and that the variance in the PL TOTAL was not significantly explained by the positional role during elite soccer match play. 1 Nevertheless, other researchers also showed that positional differences in PL TOTAL may exist across playing positions.…”
Section: Discussionsupporting
confidence: 89%
“…These tracking systems are valid and reliable instruments for tracking physical performance in soccer [ 18 ] and have been certified by the FIFA Quality Program to collect physical performance variables based on position and speed accuracy [ 19 ]. Each device was turned on 30 minutes before each match and calibrated on a Smart Station (RealTrack Systems, Almería, Spain) following the manufacturer’s instructions [ 20 ]. Furthermore, each player wore the same device in every match to reduce inter-unit error [ 4 ].…”
Section: Methodsmentioning
confidence: 99%
“…These devices were selected since previous investigations considered them as valid and reliable instruments for the collection of physical performance parameters (Bastida-Castillo et al, 2018) in addition to the approval from the FIFA Quality Programme (FIFA, 2020). Each tracking system was calibrated before the start of the match following the manufacturer's instructions (Oliva-Lozano, Maraver et al, 2020).…”
Section: Methodsmentioning
confidence: 99%